Novel therapeutic approaches for pediatric diencephalic tumors: improving functional outcomes - Cockle, Julia V.; Corley, Elizabeth A.; Zebian, Bassel; Hettige, Samantha; Vaidya, Sucheta J.; Angelini, Paola; Stone, Joanna; Leitch, R Jane; Albanese, Assunta; Mandeville, Henry C.; Carceller, Fernando; Marshall, Lynley V. (Frontiers in Oncology, 2023)
Pediatric diencephalic tumors represent a histopathologically and molecularly diverse group of neoplasms arising in the central part of the brain and involving eloquent structures, including the hypothalamic-pituitary axis (HPA), optic pathway, thalamus, and pineal gland. Presenting symptoms can include significant neurological, endocrine, or visual manifestations which may be exacerbated by injudicious intervention. Upfront multidisciplinary assessment and coordinated management is crucial from the outset to ensure best short- and long-term functional outcomes. In this review we discuss the clinical and pathological features of the neoplastic entities arising in this location, and their management. We emphasize a clear move towards ‘function preserving’ diagnostic and therapeutic approaches with novel toxicity-sparing strategies, including targeted therapies.